Immediate Catheter Directed Thrombolysis for Thromboembolic Stroke During Carotid Endarterectomy. (2016) - Fletcher, E.; Kabeer, M.; Sathianathan, J.; Muir, I.; Williams, D.; Lim, C.
Abstract : Background: Carotid artery endarterectomy (CEA) is a common procedure undertaken by vascular surgeons with over 5, 000 procedures performed annually worldwide. Published rates of perioperative stroke range from 1.3% to 6.3%. Case report: A case is presented in which on-table intra-cranial angiography and catheter directed thrombolysis were used for a thromboembolic occlusion of the distal internal carotid artery (ICA) and proximal middle cerebral artery (MCA). An 83-year-old lady developed a dense right hemiparesis while undergoing a CEA under local anaesthetic (LA). Immediate re-exploration of the endarterectomy did not reveal technical error. Intraoperative duplex scanning of the internal carotid artery revealed no detectable diastolic flow. On-table angiogram showed complete occlusion of the distal ICA and proximal MCA. Catheter directed administration of TPA was undertaken. The entire ICA and MCA were completely clear on a completion angiogram. The patient made a full neurological recovery. Discussion and conclusion: Prompt diagnosis and treatment with intraoperative catheter directed thrombolysis can resolve thromboembolic occlusion of the ICA/MCA. It is argued that performing CEA under LA is useful for immediate recognition of perioperative stroke. Furthermore, the advantage is highlighted of vascular surgeons having both the resources and skillset to perform on-table angiography and thrombolysis. Highlights: Post-CEA stroke can be effectively treated with catheter directed thrombolysis. It is important to diagnose and treat distal or intracranial thromboembolism. Rapid stroke recognition during CEA can be aided by performance under local anaesthetic. Vascular surgeons should be able to perform intraoperative angiography and thrombolysis.